KAJIAN LITERATUR UNTUK MENGATASI PERMASALAHAN MUSIK LITURGI - Maeja, Jhon Daeng (Bahasa Indonesia, 2024)
This study aims to examine the problems that arise in liturgical music. Liturgical music is an inseparable part of the liturgy. Its role is very central in the liturgy. However, there are still many devotees and liturgical practitioners who do not understand the function of liturgical music. This problem will be answered in this study. This research uses the literature review method. The study used a publish or perish application to search for keywords about liturgical music. The results showed that there are several solutions that can be done to overcome the problem of liturgical music. Optimizing liturgical music centers, inculturation of liturgical music in accordance with liturgical rules, rules on renewal in the liturgy, and formation for liturgical music actors such as the faithful, priests, choir members, musicians and observers of liturgical music are ways that can be done to overcome liturgical music problems.